Repair basic condition of red brick printing machine using axiomatic design method - Ika Alfiani Rokhmatul Islami; Ribangun Bamban Jakaria (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
Brick is a widely used building material due to its flexibility and user-friendly nature. UD. BKJ as a brick manufacturer faces challenges in meeting increasing market demand. This study aims to design an efficient brick molding tool using the Axiomatic Design method and implement it to simplify the production process. The research method used is evaluative, with data collection through interviews, observations, and questionnaires. The design of the brick molding tool is carried out by identifying customer needs, determining Functional Requirements (FRs) and Design Parameters (DPs), and mapping the relationship between FRs and DPs in the design matrix. The design results show that the designed brick molding tool is included in the uncoupled design category or ideal design, with each FR being able to be fulfilled independently by the corresponding DP. This tool is capable of producing 720 bricks per hour, increasing production efficiency by up to 116.22% compared to the manual molding process. Economic feasibility analysis shows that the investment in this tool is very financially feasible, with a payback period of around 16 days. In conclusion, the red brick molding machine designed using the Axiomatic Design method can increase production efficiency, meet customer needs, and be economically feasible for UD. BKJ